(w-2)=3

Simple and best practice solution for (w-2)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (w-2)=3 equation:


Simplifying
(w + -2) = 3

Reorder the terms:
(-2 + w) = 3

Remove parenthesis around (-2 + w)
-2 + w = 3

Solving
-2 + w = 3

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + w = 3 + 2

Combine like terms: -2 + 2 = 0
0 + w = 3 + 2
w = 3 + 2

Combine like terms: 3 + 2 = 5
w = 5

Simplifying
w = 5

See similar equations:

| 2v-3=5 | | 2x+9/2-31=0 | | 3m-6m+7=0 | | w+2=3 | | 125+0.5x=145 | | x^(2/3)=4 | | -4x+8=2(2x-4) | | -27=-x+24 | | 12-(x+3)=74 | | 1/2x-7=11-1/2x | | C=3.50+1.25(16-1) | | -12x+24y-38-5x-4y-16= | | 3x+x-5=(x-2) | | x^(1/3)=5 | | 7.6=y-4.8 | | C=3.50+1.25(m-1) | | -5.09x+2.785=5.5(2.2x-.05)-7.5x | | 3x+1=-11+2x | | X^3-3x^2-4x-70=0 | | y^2(-2+-1y)(9+-1y)=0 | | 3/8+(-4/5)+(-3/8)=5/4 | | 9*2+2y=72 | | x^4+9x^3-15x^2+15=0 | | 9x+2*0=72 | | 9*0+2y=72 | | -10x-55=75 | | x^2+2x+24=12x | | (5x^2z^5-9z^3)(-8x^6z)=0 | | 2/3y=20 | | 5.6x-5.1=1.06 | | (7y^2-4y+1)(8y^2-6y)= | | [-6]= |

Equations solver categories